Application of teachers’ pedagogical competencies at State SMA Negeri 1 Biak Kota, Biak Numfor Regency, Papua Province - Kadadi , Efendy; Mataputun, Yulius; Budiarti, Indah S. (ARKA INSTITUTE, 2025)
This study aims to describe and analyze the application of teachers’ pedagogical competencies in managing a safe and comfortable learning environment, managing effective student-centered learning, and managing assessments, feedback, and reporting oriented to the needs of students at SMA Negeri 1 Biak Kota. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews, participatory observation, and documentation studies, then analyzed through data reduction, data presentation, and conclusion drawing/verification stages. Data validity was assessed through triangulation and peer discussions. The results showed that teachers had applied pedagogical competencies well, as reflected in the management of a conducive learning environment, the use of innovative learning strategies and methods appropriate to student needs, and the implementation of assessments and feedback to improve learning outcomes. A good pedagogical application was supported by continuous coaching, peer and principal support, teacher professional awareness, and the availability of learning facilities. However, limitations in learning design, low motivation for self-development, and a lack of facilities and infrastructure remain obstacles. Therefore, it is necessary to strengthen aspects of learning innovation, including by improving training programs and providing supporting facilities to strengthen teachers’ pedagogical competencies on an ongoing basis.